APLIKASI BIO-BALL UNTUK MEDIA BIOFILTER STUDI KASUS PENGOLAHAN AIR LIMBAH PENCUCIAN JEAN - Said, Nusa Idaman (Jurnal Air Indonesia, 2005)
The textile industry is one of the most popular industries in Indonesia. Although it’s giving a positive value towards economic value, it also contributes a bed effect towards environmental quality. One of those industries is small-scale laundry industry located in Kelurahan Sukabumi Selatan, West of Jakarta. The lack of land and money, most of the jeans laundry industry throws away their wastewater straight to the river system without any process. The present study describes the application plastic media called bio-ball as a biofilter supporting media for treating of jeans laundry industry wastewater using combined anaerobic and aerobic process. The type of reactor that is used in this research is a continuous flow biological reactor which has total volume 195 litter and divided into 5 zones, i.e. presedimentation , 2 anoxic zone, aerobic zone and post sedimentation zone. Reactor effluent is recirculated into presedimentation zone with hydraulic recycle ratio (HRR) 1:1. Seeding is done in a natural way by directly flowing the domestic wastewater into reactor with retention time 72 hours, until a biofilm layer is formed on the surface of bio-ball media. Acclimatization is done gradually by replacing domestic with laundry jeans wastewater in 72 hours retention time, until domestic wastewater was 100 % replaced, The main research were conducting by continuous operation under condition 72 hours, 48 hours and 24 hours retention time. The result of experiment shows that within the combined anaerobic and aerobic process using bio-ball plastic media under conditions 1 - 3 days retention time, the removal efficiency of COD 78 – 91 %, BOD 85 – 92 %, Total Suspended Solids (TSS) 80 – 93 %, and Colour 48 – 57 % respectively. The longer retention time has resulted in higher removal efficiency